Solidarność PW . pismo OZ NSZZ "Solidarność" w Politechnice Warszawskiej, no. 3, 1981 - [ed. Z. Dargiel et al.] (KZ NSZZ "Solidarność" w Politechnice Warszawskiej, 1981)
Creation and circulation: For internal use